The efficacy of acamprosate and naltrexone in the treatment of alcohol dependence, Europe versus the rest of the world: a meta‐analysis. (17th March 2015) - Donoghue, Kim; Elzerbi, Catherine; Saunders, Rob; Whittington, Craig; Pilling, Stephen; Drummond, Colin
Abstract Aims To determine the efficacy of acamprosate and naltrexone in the treatment of those who are alcohol‐dependent in reducing lapse/relapse to alcohol consumption and treatment discontinuation, and to examine whether a proportion of the variance in study outcome can be explained by the country in which the trials have taken place. Method A systematic review and meta‐analysis of randomized controlled trials published before September 2013 was conducted. The primary outcome measures were the efficacy of acamprosate or naltrexone in reducing lapse/relapse compared to placebo in the treatment of alcohol dependence and treatment discontinuation. Twenty‐two randomized controlled trials (RCTs) of the efficacy of acamprosate met inclusion criteria for the meta‐analysis, with a total of 2649 participants in the acamprosate group and 2587 in the placebo group. Twenty‐seven RCTs of the efficacy of naltrexone met inclusion criteria for the meta‐analysis, with a total of 2253 participants in the naltrexone group and 1946 in the placebo group. A random‐effects model using a Mantel–Haenszel method was applied to conduct the meta‐analysis. Variance in study outcomes was explored using subgroup analysis of Europe versus the rest of the world (ROW). Results The risk of returning to any drinking at 6 months was significantly lower for acamprosate [risk ratio (RR) = 0.83, 95% confidence interval (CI) = 0.78–0.89]. There was little difference in the risk of participants discontinuing treatment for any reason (RR = 0.91, 95% CI = 0.83–1.00) or due to adverse events (RR = 1.30, 95% CI = 0.96–1.75) for the acamprosate compared to placebo groups. The risk of individuals returning to any drinking at approximately 3 months was reduced significantly for the naltrexone group (RR = 0.92, 95% CI = 0.86–1.00), as was the risk of individuals relapsing to heavy drinking at 3 months (RR = 0.85, 95% CI = 0.78–0.93). There was no significant difference between naltrexone and placebo for the risk of individuals discontinuing treatment for any reason (RR = 0.94, 95% CI = 0.84–1.05). There was a significantly greater risk of participants in the naltrexone group discontinuing treatment due to adverse events compared to placebo (RR = 1.72, 95% CI = 1.10–2.70). Subgroup analysis by country (Europe versus ROW) revealed no difference in risk between acamprosate and placebo for the outcomes returning to any drinking at 6 months and discontinuing treatment due to adverse events. For the outcome discontinuation of treatment for any reason, there was a significant difference in RR between Europe and the ROW (χ2 = 11.65, P <0.001) for acamprosate. Acamprosate was associated with a reduction in risk of discontinuing treatment for Europe (RR = 0.86, 95% CI = 0.79–0.95), but an increase in risk of discontinuing treatment for ROW (RR = 1.23, 95% CI = 1.03–1.48). Conclusions Both acamprosate and naltrexone appear to reduce the risk of individuals returning to drinking alcohol in those who are alcohol‐dependent. The country in which a randomized control trial (RCT) for the efficacy of acamprosate and naltrexone is completed does not appear to explain the variance in trial outcomes for returning to drinking alcohol or discontinuing drinking due to adverse effects. However, the country in which the RCT of acamprosate are completed may be important for explaining the variance between studies for the outcome 'discontinuing treatment for any reason'.